2004
DOI: 10.1038/sj.bjc.6601530
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalances associated with anaplastic transformation of follicular thyroid carcinomas

Abstract: The genetic alterations that underlie the progression of follicular thyroid carcinoma towards anaplasia are still largely uncharacterised. We compared the Comparative Genomic Hybridization (CGH) profiles of 20 follicular (FTCs), 12 poorly differentiated (PDTCs) and seven anaplastic thyroid carcinomas (ATCs), in order to identify the chromosomal imbalances potentially associated with cancer progression. We found: (i) when considering that a 'direct' transformation of FTC towards anaplasia occurs, the defined si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
27
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
5
27
0
1
Order By: Relevance
“…Comparison of our PDTC and ATC CGH results with previously reported data (Hemmer et al, 1999;Wilkens et al, 2000;Wreesmann et al, 2002;Rodrigues et al, 2004) revealed that all imbalances, described as frequently occurring in the literature, were also observed in the cell lines.…”
Section: Conventional Cytogenetic and Cgh Analysismentioning
confidence: 62%
See 4 more Smart Citations
“…Comparison of our PDTC and ATC CGH results with previously reported data (Hemmer et al, 1999;Wilkens et al, 2000;Wreesmann et al, 2002;Rodrigues et al, 2004) revealed that all imbalances, described as frequently occurring in the literature, were also observed in the cell lines.…”
Section: Conventional Cytogenetic and Cgh Analysismentioning
confidence: 62%
“…The chromosomal gains and losses observed for each of the cell lines and respective primary tumours were represented in an excel table (CGH supplementary data). Analysis of these data allowed to verify that although CGH alterations observed in the cell lines were not identical to the ones found in primary tumours, they presented major similarities, indicating that these cell lines largely reflect their primary tumour major cytogenetic imbalances.Comparison of our PDTC and ATC CGH results with previously reported data (Hemmer et al, 1999;Wilkens et al, 2000;Wreesmann et al, 2002;Rodrigues et al, 2004) revealed that all imbalances, described as frequently occurring in the literature, were also observed in the cell lines. …”
mentioning
confidence: 62%
See 3 more Smart Citations